THE FISH LANDING EFFECIENCY TIME OF BOUKE AMI (STICK HELD DIP NET) FISHING VESSELS IN THE FISHING PORT KEJAWANAN ARCHIPELAGO, CIREBON DISTRICT, WEST JAVA PROVINCE. - Samuel Megland; Syaifuddin '; T. Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTSamuel_megland@yahoo.comWhile entering the fishing season or the density of vessels which are landed, that was resulted the quality of the catches can go down, made a queue of ships, and can increase the cost of mooring boats too. Therefore, that’s make a question arises whether the landing time to bouke ami fishing boats mooring time in the port of the archipelago Kejawanan fishery has efficient, what are the effect factors of it and how much these factors make the influence. This study was conducted on 03-17 November 2014 in the fishing port Kejawanan archipelago, using the survey method.The results showed that the efficiency level of fish landing time at bouke ami fishing vessels ranged from 22.57% to 64.36% with an average of 46.69%. Dependent variables (the amount of ABK, the age of ABK, size of fleet, cathches, the distance of unloading pier and the wasted times) there is no significant differences of the efeciency level either among the time or in parsial time.Keyword: Effeciency, Fishing Port, Dependent variables